2020
DOI: 10.4193/rhin20.034
|View full text |Cite
|
Sign up to set email alerts
|

Scoping review of chronic rhinosinusitis proteomics

Abstract: Background: Progressive advances in proteomic technology has improved our understanding of the chronic rhinosinusitis (CRS) pathogenesis and endotypes. This scoping review aims to present a comprehensive and descriptive analysis of nasal mucosa and mucus proteome of CRS patients.Methodology: Studies investigating the proteome of nasal mucosa and mucus from healthy and CRS patients via mass spectrometry were included. Critical appraisal of methodological quality was conducted with extraction of protein lists. G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 25 publications
0
20
0
Order By: Relevance
“…Systems biology has provided a more holistic understanding of diseases and endotypes [81][82][83] . Proteomic analysis of nasal mucus and mucosa in CRS suggested a trend of increased presence of immunological, metabolic, tissue remodeling and apoptotic pathways in CRS 84,85 . Metabolomics analysis of low molecular weight compounds (up to 1,500 Da) has been performed in CRS 83 .…”
Section: Genomics Proteomics and Metabolomicsmentioning
confidence: 99%
“…Systems biology has provided a more holistic understanding of diseases and endotypes [81][82][83] . Proteomic analysis of nasal mucus and mucosa in CRS suggested a trend of increased presence of immunological, metabolic, tissue remodeling and apoptotic pathways in CRS 84,85 . Metabolomics analysis of low molecular weight compounds (up to 1,500 Da) has been performed in CRS 83 .…”
Section: Genomics Proteomics and Metabolomicsmentioning
confidence: 99%
“…Gel electrophoresis is the most commonly used method for protein separation in mucus proteomic studies. 6 The recovery of proteins from gel is poor for highly glocosylated and sialidated and sulphated proteins. Alternative non-gel-based separation methods include various chromatography techniques.…”
Section: Limitationsmentioning
confidence: 99%
“…Despite these limitations, we were able to identify a comprehensive catalog of proteins correlating well with previously published literature. 6 Furthermore, minimal cytokines were identified by MS analysis within nasal mucus. Yoshikawa et al found MS to be insensitive for cytokines and growth factors on account of their small size and low abundance.…”
Section: Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, single cell gene expression studies have also revealed distinct populations of epithelial cells and lymphocytes uniquely contributing to CRS pathophysiology (117,118) . Transcriptional changes have largely been validated by proteomic studies (119)(120)(121) as well as cellular and histologic studies of sinonasal mucosa which have highlighted not only importance of inflammatory dysregulation, but tissue remodeling in CRS pathophysiology (122)(123)(124)(125)(126) .…”
Section: Recent Multiomic Approaches Applied To Crs Have Revealed Novel Insights Into the Pathophysiologic Mechanisms Of Crsmentioning
confidence: 99%